2022
DOI: 10.1002/anie.202201924
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight of MOFs under Combined Mechanical and Adsorption Stimuli

Abstract: External control over the pore size of flexible metal–organic frameworks (MOFs) has recently emerged as an intriguing concept, with possible applications to gas storage and separation. In this work we present a new pressure cell capable for the first time of monitoring through in situ X‐ray powder diffraction an adsorbent powder under combined uniaxial applied mechanical stress (up to 1 GPa) and gas pressure (up to 20 bar). The combined stress–pressure clamp (CSPC) cell was successfully exploited to follow the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A study by Iacomi et al, which employed a combined stress−pressure clamp, revealed that the full reopening of the np phase triggered by adsorbing CO 2 was inhibited in proportion to the applied stress when mechanical stress up to ∼0.25 GPa and gas pressure up to 20 bar were simultaneously applied. 36 Moreover, the structural stability and compressibility of MIL-53(Al) were evaluated by in situ synchrotron powder Xray diffraction (PXRD) which suggests that MIL-53(Al) can withstand high-pressure conditions to a significant extent. Specifically, the as-made MIL-53(Al) was found to undergo a unique re-entrant negative linear compressibility (NLC) process under compression up to 41.6 GPa, supported by the subtle local structure evolution in Raman spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Iacomi et al, which employed a combined stress−pressure clamp, revealed that the full reopening of the np phase triggered by adsorbing CO 2 was inhibited in proportion to the applied stress when mechanical stress up to ∼0.25 GPa and gas pressure up to 20 bar were simultaneously applied. 36 Moreover, the structural stability and compressibility of MIL-53(Al) were evaluated by in situ synchrotron powder Xray diffraction (PXRD) which suggests that MIL-53(Al) can withstand high-pressure conditions to a significant extent. Specifically, the as-made MIL-53(Al) was found to undergo a unique re-entrant negative linear compressibility (NLC) process under compression up to 41.6 GPa, supported by the subtle local structure evolution in Raman spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the case of MIL-53, its unique structural flexibility makes it particularly intriguing for investigating the influence of pressure on the CO 2 adsorption performance. A study by Iacomi et al, which employed a combined stress–pressure clamp, revealed that the full reopening of the np phase triggered by adsorbing CO 2 was inhibited in proportion to the applied stress when mechanical stress up to ∼0.25 GPa and gas pressure up to 20 bar were simultaneously applied …”
Section: Introductionmentioning
confidence: 99%
“…Despite these achievements, the influence of pore parameters on sensing abilities of MOFs remains largely unexplored, primarily due to the intricate sensing processes involving dynamic and static interactions that match the structure and energy levels to target species [34–36] . This knowledge gap hinders comprehensive investigations into the pore effects of MOF‐based luminescent sensors [37,38] . For the selective sensing of p ‐xylene in isomers, the size and shape of the pore need to be well matched to p ‐xylene, which is highly challenging in synthetic chemistry to date (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] This knowledge gap hinders comprehensive investigations into the pore effects of MOF-based luminescent sensors. [37,38] For the selective sensing of p-xylene in isomers, the size and shape of the pore need to be well matched to p-xylene, which is highly challenging in synthetic chemistry to date (Table S1).…”
Section: Introductionmentioning
confidence: 99%